The Royal Navy North Sea War Plan 1907-1914 - Clemmesen, Michael H. (Fra Krig og Fred, 2014)
On retiring in spring 1907, Admiral Sir Arthur Wilson assisted his respected First Sea Lord, John Fisher, by consolidating their common ideas into a memorandum about how to defeat Germany quickly via the destruction of the High Seas Fleet in the North Sea, thereby creating an alternative to sending the army to the Continent. His memo mirrored the observational blockade concepts of Captain George Ballard and the work of Captain Henry Jackson on how to employ wireless telegraphy in fleet command and control.  This article follows how these ideas in interplay with experience from the annual manoeuvres influenced the developing war planning up to the start of the war in summer 1914.